Distribuição da variação genética nos canídeos Cerdocyon thous e Chrysocyon brachyurus de paisagens antropizadas da região centro-oeste e sudeste do Brasil - Rodriguez Castro, Karen Giselle (Universidade Federal de São Carlos, 2017)
The Crab-eating fox (Cerdocyon thous) and the Maned Wolf (Chrysocyon brachyurus) are a fundamental part from the habitats where they occur, due to the ecosystemic functions they play, as seed dispersers and controlling the population size of their preys. In order to protect these species is necessary to know about its genetic population structure in the current scenario of anthropized and highly transformed landscape. In this context, this work aimed to gather genetic, biological and ecological information for both species from molecular-genetic approach. Thus, we assessed and compared population sizes and densities, we evaluated genetic variation distribution and population structure, besides we evaluated possible sex-biased dispersion, and finally relatedness between and within sampled areas for both canids species. For that propose, we collected tissue, blood and scat samples of both species in three anthropic areas of three states in the central-west and southeastern regions of Brazil: Mato Grosso do Sul, Goiás and São Paulo. We extract the total DNA and amplify it for species identification (using mtDNA), for sexing (using nuclear genes) and for population genetic analyses (using microsatellites). A total of 122 Crab-eating foxes belonging to the three different sampled populations were studied. The relatedness values to Crab-eating foxes were high and migrant individuals are present among the studied areas. We found two populations for the Maned Wolfs (N=93): one including the São Paulo state individuals and the other one including Mato Grosso do Sul and Goiás individuals. The two identified populations showed no population isolation. We found a positive correlation between the geographic and genetic distances, resulting in isolation by distance in both species. Fragment size was not so important, while landscape conservation status and permeability level cause strong impacts on the genetic diversity of both species. Thus, more altered, anthropized and less permeable landscapes, such as the São Paulo state, showed genetic diversity reduction, mainly in the Maned Wolf, a solitary, more sensitive and a lower population density species. None of the species showed philopatry evidence or preferential dispersion for neither sex.
Genetic variation distribution in canids Cerdocyon thous and Chrysocyon brachyurus of antropized landscapes of central-west and southeast region of Brazil
Keywords: Amostras não invasivas; Densidade populacional; Estruturação populacional; Isolamento por distância; Microssatélites; mtDNA; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA